2006
DOI: 10.1002/gepi.20191
|View full text |Cite
|
Sign up to set email alerts
|

Sex‐specific QTL effects on variation in paraoxonase 1 (PON1) activity in Mexican Americans

Abstract: Paraoxonase 1 (PON1), a high-density lipoprotein-associated enzyme known to protect against cellular damage from toxic agents, may also have antioxidant properties. PON1 activity levels have been reported to differ by sex in human and animal studies with females exhibiting higher basal levels. We measured PON1 activity frozen serum for 1,406 individuals in over 40 extended pedigrees from the San Antonio Family Heart Study (SAFHS). We used a maximum likelihood-based, variance decomposition approach implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…The topic of gender differences in antioxidant status is complex, not sufficiently studied, and sometimes controversial. There are studies that found no gender differences (e.g., TEAC) (Rahman et al 2000 ), while others reported such sex dependence of various parameters (e.g., TEAC, PON) (Valabhji et al 2001 ; Winnier et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…The topic of gender differences in antioxidant status is complex, not sufficiently studied, and sometimes controversial. There are studies that found no gender differences (e.g., TEAC) (Rahman et al 2000 ), while others reported such sex dependence of various parameters (e.g., TEAC, PON) (Valabhji et al 2001 ; Winnier et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Male mice are more likely than female mice to become obese and to develop atherosclerosis when put on atherogenic diet 21 and thus the modest effect of human PON3 overexpression may be diluted and not obvious in the females. Sex differences in PON1 activity and expression (higher in females than in males) have been reported in both human and nonhuman animals, 22 and warrant further investigations of the interactions between gender, sex hormones and PON proteins. …”
Section: In This Issue Of Circulationmentioning
confidence: 82%
“…Details about analyses on HapMap samples are available upon request) Second, gene-regulation for many quantitative traits differs significantly between males and females. In particular, evidences suggested a differential genotype by sex interaction on variation on Paraoxonase-1 ( PON1 , a calcium dependent esterase known to have antioxidant properties) activity in Mexican American populations [35]. We tested for interaction between available functional variants on both OLR1 and PON1 from the HapMap dataset and found suggestive evidences for differences in gene-by-gender interactions in populations with different ancestry (details about analyses on HapMap samples are available upon request).…”
Section: Discussionmentioning
confidence: 98%